Two new best [27,10,9 ] codes - Peter Farkas; Sergio Herrera-Garcia (Communications - Scientific letters of the University of Zilina, 2000)
This paper presents two new [27,10,9] binary linear block codes which reach the upper bound in [1] for best known codes. They have different spectra as the known [27,10,9] codes constructed by Piret [2], Farkaš and Juling [5].